Analisis Butir Psikometri Purdue Spatial Visual Test (PSVT) - Nur’aini, Siti (UPAP Fakultas Psikologi UGM, 2018)
Abstract. Purdue Spatial Visual Test (PSVT) is a test that serves to measure visual-spatial abilities. Visual-spatial abilities are indispensable in various fields of work as well as in everyday life. Some areas of work that require visual-spatial skills are not only specific in the realm of science, technology, engineering and mathematics (STEM). Visual-spatial abilities include all mental processes. The purpose of this study was to adapt PSVT and analyze the item difficulty level, item discrimination and effectiveness of the distractor using classical test theory. PSVT reliability is tested using Cronbach's Alpha. The study conducted a reliability score with Cronbach's Alpha of 0.838. Item difficulty level showed an average of 0.5422 while the mean item discrimination of 0.418 grains indicated that PSVT was able to distinguish subjects with high and low visual-spatial ability. Based on the results of the analysis, PSVT is a good measuring tool to test the visual-spatial ability. Keywords: PSVT, Psychometric Property, Reliability, Visual-spatial